Development of a numerical simulation model for predicting the curing of ceramic systems in the stereolithography process. Issue 11 (September 2018) - Tarabeux, J.; Pateloup, V.; Michaud, P.; Chartier, T.
Abstract: The control of ceramic green parts dimensions produced by stereolithography is a central concern of the ceramic additive manufacturing industry. The presence of ceramic particles within the photopolymerizable system induces UV-laser beam scattering phenomenon, disrupting the polymerization process. This study focuses on the development of a numerical simulation model of the curing process, considering the scattering phenomenon. This paper presents each stages of the development of the numerical simulation model, supported and finally validated by experimentation on a commercial photopolymerizable alumina paste. Firstly, the numerical simulation model is presented. Then, a Greco-Latin square design of experiments is conducted to reduce the number of experiments. Subsequently, material-dependent parameters are identified through simulations and experimental measurements, and a scattering law is proposed. Finally, the simulation model enables to simulate easily and with accuracy the cure widths and the cure depth. It also provides visualization of the exposure distribution and the scattering phenomenon.